2017
DOI: 10.1016/j.rppnen.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of lung cancer in patients with pulmonary hamartomas: An evaluation of clinical, radiological, and pathological features and follow-up data of 96 patients with pulmonary hamartomas

Abstract: Our results show that patients with pulmonary hamartomas may have coexisting lung malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Thus, an incomplete excision likely explained this event. Previously published series in the English literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], considered collectively with the present in Table 4, con rmed our results. Among 1,733 patients evaluated, recurrence after excision was found in only 4 cases (0.23%).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, an incomplete excision likely explained this event. Previously published series in the English literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], considered collectively with the present in Table 4, con rmed our results. Among 1,733 patients evaluated, recurrence after excision was found in only 4 cases (0.23%).…”
Section: Discussionsupporting
confidence: 86%
“…Third, we found that PH was associated with synchronous or metachronous lung cancer in 14% of our population that is likely higher compared to the incidence of lung cancer in general Italian population considering that about 41,500 new cases of lung cancer have been estimated in 2018 as reported by the Italian Association of Medical Oncology and the Italian Association of Tumor Registries [24]. The association between PH and lung cancer has been previously reported, with an incidence ranging from 1-23% in previous studies [1][2][3][4][5][6][7][8][9]15], summarized in Table 5. Furthermore, Karasik et al [2], and Ribet et al…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pulmonary hamartomas are the most frequently diagnosed benign lung tumors that affect 2-4 times more commonly males than females. Most cases are observed in patients between 40 and 70 years of age 4 . In our series the male to female ratio was 1.4, and the mean age of the patients was 50.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a very low malignant potential, systemic workup and diagnosis are necessary, as bronchogenic carcinoma must be ruled out 10. Studies have demonstrated that hamartomas have an association with malignant lung tumours and are reported to have presented with synchronous and metachronous lung cancers 11…”
Section: Discussionmentioning
confidence: 99%